GAMBARAN TINGKAT SPIRITUAL PADA LANSIA HIPERTENSI DI WILAYAH KERJA PUSKESMAS TIRTO 1 KABUPATEN PEKALONGAN - Agustino, Dika; Natalya, Wiwiek (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
The incidence of hypertension rises with as one gets older. The phenomenon of vasoconstriction associated with aging, which leads to increased peripheral resistance, is considered a contributing factor to the development of hypertensioninolderindividuals.Peoplewhopossessarobustsense ofspiritualityare likelytoexperienceastateoftranquility,leadingtoareductionintheirblood pressure levels. The objective of this study was to provide a description of the spiritual state among elderly people with hypertension residing in the area of Public Health Center Tirto I, PekalonganRegency. Method: The present study used a descriptive research design. The sample technique employed in this study was cluster random sampling. The sample size consists of 64 respondents. The research used the Daily Spiritual Experience Scale (DSES) questionnaire, developed by Underwood and Teresi (2002), which has undergone rigorous testing to establish its validity (Pearson product moment correlation coefficient of 0.85) and reliability (Cronbach's alpha coefficient of 0.92). Results:Theresultsofthisstudyshowthattheaverageageofthe participantsis65.78 years. The majority of responders, comprising 46 participants (71.9%), identified as female. The majority of respondents (59.4%) reported having completed elementary school as their highest level of education. All participants in the study identify as Muslim, constituting 100% of the sample. A significant proportion of responders, specifically 35 individuals (54.7%), experienced hypertension over a duration of 4-6 years. The average spiritual level of the respondents was found to be 72.39. The minimum score observed was 53, while the best score recorded was88. Conclusion: The elderly with hypertension had a median spirituality score of 73.50 and a mean of 72.39. The lowest possible score is 53, and the highest possible is 88. The spiritual level is mostly good. Suggestion: The spiritual level questionnaire instrument used in this study is general spiritual, while the majority of respondents are Muslims. It is hoped that future researchers will use a questionnaire that focuses on the specific respondent's religion.